NUTRITIONAL STATUS SCREENING AND NUTRITION FULFILLMENT EDUCATION IN THE ADOLESCENT FOOTBALL CLUB IN KUBUTAMBAHAN VILLAGE - Ni Kadek Diah Purnamayanti (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2022)
Background: Adolescent boys are an age group that needs special attention regarding the fulfillment of nutrition to support activity and growth. The sport activity that is often the choice of teenage boys is soccer. This type of sport requires excellent energy and is classified as a strenuous activity Purpose: This community service activity aims to carry out early detection of the nutritional status of teenage boys who are members of soccer sports clubs. This activity also provides education to athletes and coaches in Kubutambahan Village. Methods: This activity was carried out by conducting a physical examination related to anthropometry accompanied by counseling related to the nutrition of soccer athletes. Educational content related to nutrition before the competition, before the competition and after the competition. Results: All athletes of the U21 soccer club in Kubutambahan Village are at the age of 11-16 years. The total number of youth involved in this activity is 21 people. Most (85.71%) had normal nutritional status. While 9.5% are under nutrition and 4.79% are obese. Conclusion: Early detection of nutritional status in adolescents who are members of soccer clubs is important to do. Efforts to fulfill long-term nutrition need to involve parents and sponsors in order to realize a balanced nutritional composition.